Population of Spodoptera exigua Hübner during On- and Off-Season of Shallot in Bantul Regency, Yogyakarta - Fitri Ujiyani; Y. Andi Trisyono; Witjaksono Witjaksono; Suputa Suputa (Universitas Gadjah Mada, 2019)
Beet armyworm (Spodoptera exigua Hübner) (Lepidoptera: Noctuidae) is known to be a polyphagous insect that infests many crops such as welsh onion, maize, tobacco, cotton, and others. In Indonesia, this species is a major pest of shallot. The study was aimed to monitor the population of beet armyworm in the shallot plantation in Bantul Regency, Yogyakarta. The monitoring was conducted using pheromone traps containing Z-9-tetra decanol 10 µg/rubber unit and Z-9-tetradecadienyl 90 µg/rubber unit. The pheromone was placed in the fields to trap males during on- and off-shallot plant season. The sites for placing the pheromone traps were selected in the farms where shallot was planted once and twice per year. The selected sites were with shallot and non-shallot in their surrounding areas. The result showed that males emerged both on- and off-shallot planting seasons in most of the areas. The average number of trapped males during the shallot season was < 5 males/trap/week. The number increased and reached the peak (7.33 males/trap/week) in June until July which was the off-shallot season. The population reduced to < 2 males/trap/week at the end of second shallot planting season until end of the year where the fields were mostly planted with rice. These findings indicate that the beet armyworm presents all year around with or without shallot in the fields. It suggests that management of this insect should be done not only during the shallot season but also the remaining seasons to obtain more effectiveness.